Komunikasi Organisasi di Era Digital Dalam Meningkatkan Kualitas Kepemimpinan Transformasional - La Ode Abdul Musawir; Kasman Muslimin; La Ode Ahmad Darwin; Iwan P; Rosikah Rosikah (CV. ITTC INDONESIA, 2025)
This study aims to determine Organisational Communication in the Digital era in Improving the Quality of Transformational Leadership.The method used is literature analysis with the purpose of literature. Data collection is done through systematic searches of scientific literature on related articles, books, documents, and journals that discuss significantly related to the research theme, namely Organisational Communication in the Digital era in Improving the Quality of Transformational Leadership.The results obtained that Organisational communication in the digital era has undergone a significant transformation, from face-to-face interactions to dynamic and fast virtual communication patterns. In this context, transformational leaders are required to not only understand technology, but also master digital communication strategies that are able to create emotional connections with organisational members. Leadership success is no longer determined by physical presence alone, but by the ability to present a strong vision, deliver inspiring messages, and build collaboration through various digital media. The use of platforms such as video conferencing, collaborative applications, and social media has become an important instrument in strengthening interactions and accelerating the decision-making process. The quality of transformational leadership depends on the leader's ability to combine technological aspects and human values in communication. Leaders who are able to maintain message authenticity, show empathy, and adapt their communication style to the digital context will be more effective in driving change and motivating organisational members. The digital age is not a barrier to transformational leadership, but a great opportunity to expand influence, accelerate innovation, and strengthen working relationships across distance and time. Adaptive, strategic and human relations-oriented organisational communication is a key foundation in shaping transformative and relevant leadership today.